2012
DOI: 10.1007/s11250-012-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bypass fat supplementation on productive performance and blood biochemical profile in lactating Murrah (Bubalus bubalis) buffaloes

Abstract: The study investigated the effect of dietary supplementation of bypass fat on productive performance and blood biochemical profile of lactating Murrah buffaloes (Bubalus bubalis). Fifteen multiparous buffaloes (2-4 lactation) of early to mid lactation were divided in three homogenous groups T(1) (control), T(2), and T(3) of five each. The animals in T(1) were fed with a basal diet consisting of a concentrate mixture, green sorghum, and wheat straw as per requirements, while the animals in group T(2) and T(3) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 12 publications
8
20
0
4
Order By: Relevance
“…The overall mean plasma total cholesterol value in the cows supplemented was observed to be significantly higher (p<0.01) as compared to control group which was substantiated by the observations of Tyagi et al (2010) and Ranjan et al (2012). Dietary fat increases circulating concentrations of cholesterol (Staples and Thatcher, 2005) and progesterone and the lifespan of induced CL in cattle.…”
Section: Plasma Protein and Cholesterol Profilesupporting
confidence: 64%
“…The overall mean plasma total cholesterol value in the cows supplemented was observed to be significantly higher (p<0.01) as compared to control group which was substantiated by the observations of Tyagi et al (2010) and Ranjan et al (2012). Dietary fat increases circulating concentrations of cholesterol (Staples and Thatcher, 2005) and progesterone and the lifespan of induced CL in cattle.…”
Section: Plasma Protein and Cholesterol Profilesupporting
confidence: 64%
“…It was noticed that average weekly milk yield showed that Bypass fat supplementation at 1.4% of DMI (200 g day -1 ) increased the milk production and feed efficiency in lactating Murrah buffaloes (Ranjan et al, 2012). There was an improvement of 6.02% in milk yield of early lactating crossbred cows fed 75 g day -1 per animal PF (Rajesh, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Para os ácidos graxos saturados, a elevação de consumo foi de 71,23% nos animais tratados (132,07 versus 77,14g/animal/dia). Gandra et al (2011) (6,56mg/dL) e Ranjan et al (2012) (16,27mg/dL), estes últimos tendo fornecido gordura protegida para fêmeas bubalinas em lactação. A presença de receptores para VLDL em espermatozoides sugere que estes utilizam lipídios extracelulares, estando o papel desses receptores associado ao prolongamento da utilização de energia e ao provimento para o espermatozoide de metabólitos essenciais, tais como triglicérides, fosfolípides e ácidos graxos (Argov et al, 2007), com maior eficiência na utilização de energia.…”
Section: Discussionunclassified
“…Entretanto, os dados observados foram distintos dos previamente publicados para touros bubalinos, de 213,26 mg/dL e 324,74±3,81mg/dL (Ranjan et al, 2012;Nalavade et al, 2002). Sob esse prisma, incrementos nos lipídios séricos totais, caso associados a um aumento paralelo nas concentrações de lipídios totais no plasma seminal, como ocorre em bovinos (Beer-Ljubic et al, 2009), poderiam representar uma ameaça à integridade da membrana espermática.…”
Section: Discussionunclassified
See 1 more Smart Citation